Kemampuan Membaca Kritis pada Mata Pelajaran Bahasa Indonesia Materi Teks Narasi Bandung Lautan Api Kelas V SD Negeri 1 Majan - Shelsa Dyah Aprillia; Nourma Okaviarini (Journal on Education, 2024)
Critical reading is a type of reading that is done wisely, tolerantly, deeply, evaluatively, and analytically, and not just looking for mistakes. Students have used critical reading in reading a passage but only a few indicators are used, namely interpreting the explicit meaning, assessing the content of the reading and citing the content of the reading only. Students also use reading aloud and reading silently. Reading learning is still not optimal because during the learning process the class situation is not conducive and there are some students who often lose focus in learning. This type of research is descriptive qualitative. Data collection using tests, observation and documentation. The results of this study found that the total score of critical reading skills was 311 and the overall percentage of critical reading skills was 67.58% in the good category. This is obtained from aspect 1, namely interpreting the explicit meaning, getting a total score of 69 and a percentage of 75% of 23 students who fall into the good category. Aspect 2, namely applying concepts in reading, received a total score of 50 with a percentage of 54.3% of 23 students in the moderate category. Aspect 3, analyzing the content of the reading, received a total score of 60 with a percentage of 65.2% of 23 students in the good category. Aspect 4, analyzing the content of the reading, received a total score of 59 with a percentage of 64.1% of 23 students in the sufficient category. Aspect 5 assessing the content of the reading received a total score of 73 with a percentage of 79.3% of 23 students in the good category.